Colonoscopist and Primary Care Physician Supply and Disparities in Colorectal Cancer Screening - Benarroch-Gampel, Jaime (Blackwell Science Inc, 2012)
OBJECTIVE: To determine whether racial/ethnic disparities in colonoscopy use vary by physician availability. DATA SOURCE: We used 100 percent Texas Medicare claims data for 2003–2007. STUDY DESIGN: We identified beneficiaries aged 66–79 in 2007, examined racial/ethnic differences in colonoscopy use from 2003 to 2007, and estimated the percentage of white, black, and Hispanic beneficiaries who underwent colonoscopy by level of physician availability and area income. PRINCIPAL FINDINGS: For the 974,879 beneficiaries, colonoscopy use was higher in whites (40.7 percent) compared to blacks (35.0 percent) and Hispanics (28.7 percent, p < .001). For whites, increasing availability of colonoscopists and primary care physicians (PCPs) was associated with higher colonoscopy use. For blacks and Hispanics, colonoscopy use was unchanged or decreased with increases in colonoscopist and PCP availability. In multilevel models, the odds of colonoscopy were 20 percent lower for blacks (OR 0.80, 95 percent CI 0.79–0.82) and 32 percent lower for Hispanics (OR 0.68, 95 percent CI 0.66–0.69) compared to whites; adjusting for availability of colonoscopists or PCPs did not attenuate racial/ethnic disparities. We found greater racial/ethnic disparities in areas with greater colonoscopist and PCP availability. CONCLUSIONS: Greater area availability of colonoscopists and PCPs is associated with increased use of colonoscopy in whites but decreased use in minorities, resulting in larger racial/ethnic disparities.